Witnessing in a Time of Homeland Futurities - Fukushima, Annie (Anti-Trafficking Review, 2020)
Current US rhetorical strategies of imagining a future of the homeland have led to the creation and utilisation of new technologies to contain and manage the border. These responses to the US border and immigration impact anti-trafficking efforts, sustaining a ‘homeland futurity’. Homeland futurity draws on and extends discourses of emergency that solidify borders as dangerous and risky. This article traces how homeland futurities emerged in US anti-trafficking efforts. Drawing upon interviews and focus group discussions with service providers and survivors of violence in San Francisco, the article demonstrates how migrant labourers are impacted by a discourse of threat and containment of the border. However, migrant labourers and their allies are innovating to secure a life that mitigates risk through migrant labourers’ use of technology. This article illustrates through the example of Contratados.org how technology may facilitate opportunities of future visioning by migrant labourers beyond a homeland futurity, to enact practices that bring to the centre migrants and their experiences through social networking and information sharing on job prospects.